The Maximum Number of Appearances of a Word in a Grid. Issue 5 (10th May 2022) - Patchell, Gregory; Spiro, Sam
Abstract: How can you fill a 3 × 3 grid with the letters A and M so that the word "AMM" appears as many times as possible in the grid? More generally, given a word w of length n, how can you fill an n × n grid so that w appears as many times as possible? We solve this problem exactly for several families of words, and we asymptotically solve this problem in higher-dimensional grids.